2003
DOI: 10.1080/00365590310004725
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Evaluation of Occult Spinal Dysraphism in 47 Children

Abstract: In the light of our findings and the literature data it is obvious that a multidisciplinary approach together with early urologic evaluation to determine the extent of neurologic involvement of the lower urinary tract is essential to ensure a successful treatment outcome and to prevent the occurrence of serious functional and structural complications. Clinical, radiologic and video-urodynamic assessments should be performed to define the neuro-urologic pathophysiology and to provide management guidelines and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Current case series is from countries with relatively high prevalence of BD (420 per 100,000 population in Turkey; 80 per 100,000 population in Iran) [16][17][18]. On the other hand, ALS is relatively rare in these countries (1.57 per 100,000 population in Iran [19]).…”
Section: Discussionmentioning
confidence: 99%
“…Current case series is from countries with relatively high prevalence of BD (420 per 100,000 population in Turkey; 80 per 100,000 population in Iran) [16][17][18]. On the other hand, ALS is relatively rare in these countries (1.57 per 100,000 population in Iran [19]).…”
Section: Discussionmentioning
confidence: 99%
“…Regular follow-up by specialized nurse practitioners, and enhancing motivation in the parents and children were also influential factors. 21 Despite good clinical effects, some children and parents using transanal irrigation found this method very time consuming and too complicated for self-management. To improve this discomfort, it may be important to start a bowel management program initially and provide sufficient time and support to help children with neurogenic bowel disturbance to be independent at the toilet.…”
Section: Discussionmentioning
confidence: 99%
“…Other important factors that could have affected this result were the financial, social, economic, educational and intellectual level of the newborns’ families. The rate of spinal-dysraphism-related nervous system abnormalities in neonates with a single and small lesions is low [26]; however, the study of 171 neonates who had spinal dysraphism abnormalities showed that multiple skin lesions, large subcutaneous masses and cutaneous sinuses over the sacrum were correlated with an increase in the rate of spinal dysraphism disorders. Henriques et al [10] also prospectively studied minor skin lesions as signs of spinal dysraphism by spinal USG.…”
Section: Discussionmentioning
confidence: 99%